2013
DOI: 10.1002/glia.22516
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of P2X4 receptors in hippocampal microglial activation afterstatus epilepticus

Abstract: Within the central nervous system, functions of the ATP-gated receptor-channel P2X4 (P2X4R) are still poorly understood, yet P2X4R activation in neurons and microglia coincides with high or pathological neuronal activities. In this study, we investigated the potential involvement of P2X4R in microglial functions in a model of kainate (KA)-induced status epilepticus (SE). We found that SE was associated with an induction of P2X4R expression in the hippocampus, mostly localized in activated microglial cells. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 40 publications
4
88
0
Order By: Relevance
“…Brain inflammation can affect both excitotoxicity-mediated neurodegeneration (Vezzani, 2005;Ulmann et al, 2013) as well as modulate the seizure-induced neurogenesis (Jakubs et al, 2006;Ekdahl et al, 2009). Acute microglial activation following epileptic seizures is detrimental to the survival of newly formed neurons (Ekdahl et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Brain inflammation can affect both excitotoxicity-mediated neurodegeneration (Vezzani, 2005;Ulmann et al, 2013) as well as modulate the seizure-induced neurogenesis (Jakubs et al, 2006;Ekdahl et al, 2009). Acute microglial activation following epileptic seizures is detrimental to the survival of newly formed neurons (Ekdahl et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…PI3K/Akt and integrins play a crucial role in actin filament remodeling (41,42), which presumably underlies their role in promoting targeted microglial process motility on P2Y 12 receptor activation. In addition to P2Y 12 , P2X 4 receptors might contribute to ATP-evoked chemotaxis of microglia in vitro (30), but expression of P2X 4 in situ only occurs after microglial activation, not in quiescent, ramified microglia (35).…”
Section: Purinergic Signaling Involved In Microglia Chemotaxismentioning
confidence: 97%
“…Microglia in situ use ionotropic P2X and metabotropic P2Y and P1 receptors to respond to extracellular nucleotides and nucleosides such as ATP (P2X 4 , P2X 7 , P2Y 2 ), ADP (P2Y 12 , P2Y 13 ), UTP (P2Y 2 , P2Y 4 ), UDP (P2Y 6 ), and adenosine (P1) (6,23,29,(31)(32)(33)(34)(35). ATP is the main nucleotide released upon tissue injury, and the extracellular concentration reached may be amplified by astrocytes releasing further ATP (4,10).…”
Section: Purinergic Signaling Involved In Microglia Chemotaxismentioning
confidence: 99%
“…Within this circuitry, P2X4Rs have been localized to these regions either within neurons (Rubio and Soto, 2001) or glia (both microglia and astrocytes) (Rubio and Soto, 2001; Ulmann et al, 2008, 2013), implicating a role in reward- and aversion-related neurotransmission, as well as cellular immune activity. Functional studies also have reported that P2X4Rs can play an important role in the reward circuitry by regulating the release of glutamate (Krugel et al, 2004; Khakh, 2009) or dopamine (Krugel et al, 2003; Kittner et al, 2004) within the VTA and NAcc.…”
Section: Overview Of Purinergic Receptorsmentioning
confidence: 99%